2016
DOI: 10.1016/j.bbrc.2016.06.157
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by 6-gingerol in diabetic rats

Abstract: The current study was conducted to evaluate the effect of 6-gingerol (6G) on cardiac complications in streptozotocin (STZ)-induced diabetic (DM) rats. STZ-induced DM rats (single 50 mg/kg i.p. injection, 15 days prior to drug treatment) or time-matched controls were treated with 6G (75 mg/day route orally). After a further 8 weeks, blood was collected for biochemical analysis and 8-isoprostenol was measured in urine. Cardiac hemodynamics and ECG was assessed. 6G significantly attenuated the increased level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Diabetes mellitus (DM) is the most common type of metabolic disorders and a leading cause of CVD. 73 It was shown that the activation of several signaling pathways, such as NF-κB, p38-MAPK, or c-jun NH2-terminal kinase could mediate a state of inflammation that is linked to insulin resistance and diabetic complications. Activation of NF-κB is associated with the increased release of TNF-α, which is regarded as a key factor in cardiac damage and leads to further NF-κB activation, thus contributing to the intensification of adverse effects in the diabetic heart.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Diabetes mellitus (DM) is the most common type of metabolic disorders and a leading cause of CVD. 73 It was shown that the activation of several signaling pathways, such as NF-κB, p38-MAPK, or c-jun NH2-terminal kinase could mediate a state of inflammation that is linked to insulin resistance and diabetic complications. Activation of NF-κB is associated with the increased release of TNF-α, which is regarded as a key factor in cardiac damage and leads to further NF-κB activation, thus contributing to the intensification of adverse effects in the diabetic heart.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…It can inhibit platelet aggregation and improve ventricular systolic and diastolic function. Simultaneously, ZR can also reduce peripheral resistance, which has a protective effect on the formation of acute heart failure (AHF) model . According to the theory of traditional Chinese medicine (TCM), both ALRP and ZR are pungent in taste and hot in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, interest in 6‐gingerol as a potential therapeutic has increased over the years due to its safety, efficacy, and control of multiple targets . Several studies have shown that 6‐gingerol may regulate plasma adiponectin level related to the beneficial effects in insulin sensitivity and hyperlipidemia . Moreover, 6‐gingerol reduces blood glucose levels in diabetic animal models and promotes glucose uptake in L6 myotubes, which involve AMPKα activation .…”
Section: Introductionmentioning
confidence: 99%